2021
DOI: 10.1101/2021.01.22.427802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human airway cells prevent SARS-CoV-2 multibasic cleavage site cell culture adaptation

Abstract: Virus propagation methods generally use transformed cell lines to grow viruses from clinical specimens, which may force viruses to rapidly adapt to cell culture conditions, a process facilitated by high viral mutation rates. Upon propagation in VeroE6 cells, SARS-CoV-2 may mutate or delete the multibasic cleavage site (MBCS) in the spike protein that facilitates serine protease-mediated entry into human airway cells. We report that propagating SARS-CoV-2 on the human airway cell line Calu-3 - that expresses se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 33 publications
(25 reference statements)
4
32
0
Order By: Relevance
“…Finally, as also observed by others [32-34, 53], we found that in-frame deletions of the furin-cleavage site in S could be selected for and enriched in SARS-CoV-2 isolates during passage in Vero-CCL81 cells. This was apparent even for very low passage stocks as described here (passage 3 from original patient material), but importantly was not a universal feature of all SARS-CoV-2 isolates: deletions of the S furin-cleavage site were only detected in 2 out of 14 of our primary isolates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Finally, as also observed by others [32-34, 53], we found that in-frame deletions of the furin-cleavage site in S could be selected for and enriched in SARS-CoV-2 isolates during passage in Vero-CCL81 cells. This was apparent even for very low passage stocks as described here (passage 3 from original patient material), but importantly was not a universal feature of all SARS-CoV-2 isolates: deletions of the S furin-cleavage site were only detected in 2 out of 14 of our primary isolates.…”
Section: Discussionsupporting
confidence: 86%
“…Such findings, together with our additional observations relating to functional E substitutions during SARS-CoV-2 growth in Vero-CCL81 cells, underscore the need for care during stock preparation, particularly where viruses are to be compared with one another for phenotypes. Thus, it may be that other cell-lines, including human Calu-3 [53], are more suitable for SARS-CoV-2 propagation, and should be thoroughly characterized in the future as a possible substrate to limit cell culture adaptation in SARS-CoV-2 genes such as S and E. Nevertheless, we found that in-frame deletions in the S furin-cleavage site attenuated SARS-CoV-2, most notably in primary human bronchial epithelial cells. However, passaging of SARS-CoV-2 preparations containing the S furin-cleavage site deletions in primary human bronchial epithelial cells provided a very high selection pressure to enrich only for viruses that retained the full S furin-cleavage site.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as also observed by others [32][33][34]53], we found that in-frame deletions of the furin cleavage site in S could be selected for and enriched in SARS-CoV-2 isolates during passage in Vero-CCL81 cells. This was apparent even for very low-passage stocks as described here (passage 3 from original patient material), but importantly was not a universal feature of all SARS--CoV-2 isolates: Deletions of the S furin cleavage site were only detected in 2 out of 14 of our primary isolates.…”
Section: Plos Biologysupporting
confidence: 87%
“…Such findings, together with our additional observations relating to functional E substitutions during SARS-CoV-2 growth in Vero-CCL81 cells, underscore the need for care during stock preparation, particularly where viruses are to be compared with one another for phenotypes. Thus, it may be that other cell lines, including human Calu-3 [53], are more suitable for SARS-CoV-2 propagation and should be thoroughly characterized in the future as a possible substrate to limit cell culture adaptation in SARS-CoV-2 genes such as S and E. Nevertheless, we found that in-frame deletions in the S furin cleavage site attenuated SARS-CoV-2, most notably in primary human BEpCs. However, passaging of SARS-CoV-2 preparations containing the S furin cleavage site deletions in primary human BEpCs provided a very high selection pressure to enrich only for viruses that retained the full S furin cleavage site.…”
Section: Plos Biologymentioning
confidence: 79%
“…Epithelial organoids have gained traction as a physiological platform for personal medicine because these organoids retain patient-specific traits 19 . A handful of studies have used alveolospheres and organoids to study SARS-CoV-2 epithelial response 20,21,22,23,24,25 and tropism 7, 26,27,28,29,30 . A comprehensive analysis of SARS-CoV-2 infection in a large panel of lung organoids has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%